3-(2-Fluoroanilino)Isobenzofuran-1(3H)one - Odaba̧soǧlu, M.; Büyuk̈güngör, O. (Int Union Crystallography, 2007)
The crystal structure of the title compound, C14H10FNO2, is stabilized by N - H⋯O, two C - H⋯O and two C - H⋯F inter-molecular hydrogen bonds. N - H⋯O, C - H⋯O and two C - H⋯F inter-molecular hydrogen bonds generate a fused R 2 2(10)R 2 2(12)R 2 2(15)R 3 2(13) ring motif. In the crystal structure, mol-ecules are linked into chains along the b axis by C - H⋯O hydrogen bonds. The dihedral angle between the phthalide group and the other benzene ring is 73.51 (5)°. © International Union of Crystallography 2007.